Mouse S100G protein exhibits properties characteristic of a calcium sensor. (May 2020) - Permyakov, Sergei E.; Yundina, Elena N.; Kazakov, Alexei S.; Permyakova, Maria E.; Uversky, Vladimir N.; Permyakov, Eugene A.
Graphical abstract: Highlights: Mouse S100 G is a member of the EF-hand family of calcium binding proteins. Contrary to bovine S100 G structure and function of mouse protein depends on calcium. Based on its response to calcium, mouse S100 G is classified as calcium sensor protein. Apo-form of mouse S100 G has the properties of highly ordered molten globule. Mouse S100 G is predicted to contain high levels of intrinsic disorder. Abstract: Bovine S100 G (calbindin D9k, small Ca 2+ -binding protein of the EF-hand superfamily) is considered as a calcium buffer protein; i.e., the binding of Ca 2+ practically does not change its general conformation. A set of experimental approaches has been used to study structural properties of apo- and Ca 2+ -loaded forms of mouse S100 G (81.4% identity in amino acid sequence with bovine S100 G). This analysis revealed that, in contrast to bovine S100 G, the removal of calcium ions increases α-helices content of mouse S100 G protein and enhances its accessibility to digestion by α-chymotrypsin. Furthermore, mouse apo-S100 G is characterized by a decreased surface hydrophobicity and reduced tendency for oligomerization. Such behavior is typical of calcium sensor proteins. Apo-state of mouse S100 G still has rather compact structure, which can be cooperatively unfolded by temperature and GdnHCl. Computational analysis of amino acid sequences of S100 G proteins shows that these proteins could be in a disordered state upon a removal of the bound calcium ions. The experimental data show that, although mouse apo-S100 G is flexible compared to the Ca 2+ -loaded state, the apo-form is not completely disordered and preserves some cooperatively meting structure. The origin of the unexpectedly high stability of mouse S100 G can be rationalized by an exceptionally strong association of its N- and C-terminal parts containing the EF-hands I and II, respectively.